Meningeal Infiltration of the Spinal Cord by Non-Classically Activated B Cells is Associated with Chronic Disease Course in a Spontaneous B Cell-Dependent Model of CNS Autoimmune Disease - Dang, Amy K.; Tesfagiorgis, Yodit; Jain, Rajiv W.; Craig, Heather C.; Kerfoot, Steven M. (Frontiers in Immunology, 2015)
We characterized B cell infiltration of the spinal cord in a B cell-dependent, spontaneous model of central nervous system (CNS) autoimmunity that develops in a proportion of mice with mutant T and B cell receptors specific for myelin oligodendrocyte glycoprotein (MOG). We found that, while males are more likely to develop disease, females are more likely to have a chronic rather than monophasic disease course. B cell infiltration of the spinal cord was investigated by histology and FACs. CD4+ T cell infiltration was pervasive throughout the white and in some cases grey matter. B cells were almost exclusively restricted to the meninges, often in clusters reminiscent of those described in human multiple sclerosis (MS). These clusters were typically found adjacent to white matter lesions and their presence was associated with a chronic disease course. Extensive investigation of these clusters by histology did not identify features of lymphoid follicles, including organization of T and B cells into separate zones, CD35+ follicular dendritic cells (FDCs), or germinal centers (GCs). The majority of cluster B cells were IgD+ with little evidence of class switch. Consistent with this, B cells isolated from the spinal cord were of the naïve/memory CD38hi CD95lo phenotype. Nevertheless, they were CD62Llo and CD80hi compared to lymph node B cells suggesting that they were at least partly activated and primed to present antigen. Therefore, if meningeal B cells contribute to CNS pathology in autoimmunity, follicular differentiation is not necessary for the pathogenic mechanism.